Security of the person and criminal remedies for its provision - Demieva, Ainur Gabdulbarovna; Iroshnikov, Denis Vladimirovich; Pantyukhina, Inga Vladimirovna (Opción, 2019)
The study aims to investigate the security of the person and criminal remedies for its provision via the dialectical method of scientific knowledge, the methods of analysis, synthesis, induction, deduction, as well as the method of scientific modeling. As a result, the provisions establishing criminal liability for sexual abuse through the Internet have been included in criminal laws of the countries of the European Union. The authors concluded that the time has come to replace in the Russian criminal law the title of Section VII Crimes against the Person with the title Crimes against the Security of the Person.